2015
DOI: 10.1152/ajplung.00283.2014
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β induces microRNA-29b to promote murine alveolar macrophage dysfunction after bone marrow transplantation

Abstract: Moore BB. Transforming growth factor-␤ induces microRNA-29b to promote murine alveolar macrophage dysfunction after bone marrow transplantation. Am J Physiol Lung Cell Mol Physiol 308: L86 -L95, 2015. First published October 31, 2014 doi:10.1152/ajplung.00283.2014.-Hematopoietic stem cell transplantation (HSCT) is complicated by pulmonary infections that manifest posttransplantation. Despite engraftment, susceptibility to infections persists long after reconstitution. Previous work using a murine bone marrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…Thus, it is likely that the conditioning regimen followed by an infectious stimulus is necessary to drive full elaboration of the Th17 response. In this regard, we have previously shown that lung epithelial cells are potent producers of TGFβ post-BMT, further, CD11c+ cells isolated from γHV-68 infected BMT mice secrete pro-Th17 cytokines such as IL-6, IL-23, and TGFβ which could help promote robust Th17 responses 27 , 40 .…”
Section: Discussionmentioning
confidence: 95%
“…Thus, it is likely that the conditioning regimen followed by an infectious stimulus is necessary to drive full elaboration of the Th17 response. In this regard, we have previously shown that lung epithelial cells are potent producers of TGFβ post-BMT, further, CD11c+ cells isolated from γHV-68 infected BMT mice secrete pro-Th17 cytokines such as IL-6, IL-23, and TGFβ which could help promote robust Th17 responses 27 , 40 .…”
Section: Discussionmentioning
confidence: 95%
“…TGF-␤1 is an important modulator of T cell differentiation (17) and has been shown to antagonize DNMT1 accumulation in T cells (60), where DNMT1 plays a critical role in T cell development (61). In alveolar macrophages, we previously showed that TGF-␤1 increased the expression of DNMT1 by inhibiting expression of microRNA-29b (62). microRNA-148b and microRNA-152 have also been shown to inhibit DNMT1 The mean densitometric values of phosphorylated GSK-3␤ from seven independent experiments are shown below a representative immunoblot.…”
Section: Discussionmentioning
confidence: 99%
“…miR-29b is another miRNA whose expression in MΦs has been reported to be upregulated by TGF-β. Furthermore, this has been linked to the defective functioning of MΦs after bone marrow transplantation ( 89 ). Here, miR-29b upregulates COX-2 expression via indirect means resulting in MΦs with lesser bactericidal activity.…”
Section: Anti-inflammatory Polarizationmentioning
confidence: 99%